A novel mushroom (Auricularia polytricha) glycoprotein protects against lead-induced hepatoxicity, promotes lead adsorption, inhibits organ accumulation of lead, upregulates detoxifying proteins, and enhances immunoregulation in rats - Zhao, Shuang; Gao, Yi; Wang, Hexiang; Fan, Yangyang; Wang, Pan; Zhao, Wenting; Wong, Jack Ho; Wang, Dan; Zhao, Xiaoyan; Ng, Tzi Bun (Frontiers in Nutrition, 2023)
Lead is a ubiquitous environmental and industrial pollutant. Its nonbiodegradable toxicity induces a plethora of human diseases. The current study was undertaken to purify a novel 252-kDa bioactive glycoprotein containing 1.15% carbohydrate from the edible fungus Auricularia polytricha with the ability of adsorbing lead and effecting detoxification. The A. polytricha detoxifying glycoprotein (APL), which displayed unique molecular properties, was isolated using chromatographic techniques. For investigating the protective effects of A. polytricha, Sprague Dawley (SD) rats were divided into six groups which received daily intraperitoneal injections of lead acetate for 30 days, followed by gastric gavage with APL (40, 80, 160 mg/kg B body weight) or EDTA (300 mg/kg body weight) for 30 days after successful establishment of an animal model of lead detoxification. The serum concentrations of lead and the liver biomarkers AST and ALT were significantly (p<0.05) improved by APL treatment, as well as treatment with the positive control EDTA. Likewise, results on lead residue showed that the clearance ratios of the liver and kidneys were respectively 44.5% and 18.1% at the high APL dosage, which was even better than the corresponding data for EDTA. Proteomics disclosed that 351 proteins were differentially expressed due to lead exposure and the expression levels of 41 proteins enriched in the pathways mainly involved in cell detoxification and immune regulation were normalized after treatment with APL-H. The results signify that APL may ameliorate lead-induced hepatic injury by positive regulation of immune processing, and suggest that APL be applied as a therapeutic intervention of lead poisoning in clinical treatment. This report represents the first demonstration of the protective action of a novel mushroom protein on lead-elicited hepatic toxicity.